Kinetics of the Normal Folate Enterohepatic Cycle - Stephen E. Steinberg; Caryl L. Campbell; Robert S. Hillman (1979)
Detailed studies were undertaken to better define the role of the liver and the folate enterohepatic cycle in folate homeostasis. Three isotopes of folate were employed in a rat model to study several parameters: (a) intestinal transport; (b) variation in hepatic uptake after different routes of administration; (c) hepatic reduction, methylation, and polyglutamate formation; (d) biliary excretion; (e) transport of folate to tissue and its return to liver for re-entry into the enterohepatic cycle.